Action research with local forest users and managers: global lessons from CIFOR’s research on Adaptive Collaborative Management - Prabhu, Ravi; Colfer, C.J.P.; Diaw, C.; McDougall, C.; Fisher, R. (Practical Action Publishing, 2009)
Carrying out action research with forest dependent communities calls for special attention to their tenure arrangement, power relations, heterogeneity and the governance arrangements of the forests they use or manage. This is what over four years of CIFOR s research on adaptive collaborative management (ACM) of forests in eleven countries reveals. Using examples from three of those countries we show how important it is to address passiveness, power relations and social and institutional capitals during a process of action research, and participatory action research, aimed at improving livelihoods, equity and forest systems. The ACM research also shows that processes of change tend to be slow, and four years is barely enough to bring about observable changes. The most sensitive livelihood capitals to the action research, possibly because they were primary foci of the research, were human and social capitals. The ACM research shows the importance of shared or social learning as a driver of change in the action research. We conclude that using action research with forest dependent people, groups and organizations is a viable approach to generating both change and understanding about the people and the forest systems.